The Effect of Sharia Monetary Policy and Financing Quality on Financial Performance in Sharia Banking - Muhfiatun Muhfiatun (Shirkah: Journal of Economics and Business, 2016)
The purpose of this research is to explain the effect of sharia monetary policy instruments and financing quality on the financial performance of sharia banks. The research sample includes Bank Muamalat Indonesia, Bank Syariah Mandiri, Bank Mega Syariah Indonesia, Bank Rakyat Indonesia Syariah, Bank Syariah Bukopin, BCA Syariah, BNI Syariah, and Bank Jabar Banten Syariah. The financial ratios used in this research are Return on Assets (ROA) and Quick Ratio (QR). The financing qualities used here are murabahah, mudharabah, and musharakah. The sharia monetary policy instruments used are GWM and SBIS. The research uses Partial Least Squares as the data analysis instrument. The research result shows that the financing qualities of mudharabah and musharakah, and SBIS, do not affect ROA, while the variables of murabahah financing and GWM do affect ROA. The variable with significant effect on QR is ROA, as murabahah financing quality; GWM and SBIS; and the other two variables of musharakah and mudharabah do not affect QR. The contribution of the financing quality variables of murabahah, mudharabah, musharakah, GWM and SBIS in explaining the effect on the ROA variable is 0.071 or 7.1%, and the other 92.9% are affected by other variables not in the current research model. The contribution of murabahah, mudarabah and musyarakah, GWM and SBIS in explaining the effect on QR is 0.7578 or 75.78% and the remaining 24.22% is the effect of other variables not in this research model.   Keywords: financing quality, sharia monetary policy instrument, financing performance, ROA